Traditional herbal medicine for opioid-induced constipation in patients with cancer: a systematic review and meta-analysis of randomized controlled trials - Lee, Su Hyeon; Jin, Hayun; Kim, Eun Hye; Yoon, Seong Woo (Frontiers in Pharmacology, 2026)
IntroductionThis systematic review and meta-analysis aimed to evaluate the efficacy and safety of traditional herbal medicine (THM) in improving opioid-induced constipation (OIC) in patients with cancer.MethodsTo identify randomized controlled trials (RCTs) evaluating orally administered THM for OIC in patients with cancer, a comprehensive search of seven databases was conducted from inception to 29 August 2024. The primary outcome was improvement in OIC, which was assessed using the total effective rate (TER). Secondary outcomes included stool form, difficulty of defecation, defecation time, and the Karnofsky performance scale (KPS). The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool, and the certainty of evidence was evaluated according to the Grading of Recommendations Assessment, Development, and Evaluation method.ResultsIn total, 21 RCTs involving 2,108 patients were included. Compared to conventional medicine, THM significantly improved OIC as measured by TER [risk ratio (RR) 1.21, 95% confidence intervals (CIs) 1.14–1.25], with high certainty. THM showed a significant improvement in stool form [mean difference (MD) −0.16, 95% CIs −0.43–0.10; very low certainty], difficulty of defecation [MD -0.31, 95% CIs −0.49 to −0.13; low certainty], defecation time [MD -0.28, 95% CIs −0.45 to −0.10; moderate certainty], and KPS measured by mean changes in scores [MD 6.76, 95% CIs 4.32–9.20; low certainty]. Adverse events were mainly gastrointestinal symptoms such as diarrhea, nausea, and abdominal pain, but such events were not serious.ConclusionThe findings of this systematic review indicate that THM may be considered a safe and potentially alternative option for improving OIC in patients with cancer. However, more robust and high-quality RCTs are required to strengthen this evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, Identifier: CRD42024557773.